Synthesis, crystal structure, and theoretical studies of a macrocyclic silver(I) complex of imino-pyridyl Schiff base ligand - Mondal, Jahangir; Sahu, Meman; Sharma, Bhaskar; Ganguly, Rakesh; Chowdhury, Shubhamoy; Patra, Goutam Kumar (European Journal of Chemistry, 2021)
The synthesis and characterization of an imino-pyridyl ligand N,N’-(butane-1,4-diyl)bis(1-(pyridin-2-yl)methanimine) (L) and its Ag(I)ClO4 complex (I) by various spectroscopic techniques and elemental analyses is presented in this study. X-ray single crystal structure of complex I revealed that in complex I, each Ag(I) ion is tetra coordinated with two pyridine N-atoms and two imine N-atoms of the ligand L, forming a macrocyclic dimeric Ag(I) grid. In the macrocyclic dimer complex I, Ag-Ag separation along the chain is 5.318 Å. The Ag-Npy average distance is 2.396 Å and that of the Ag-Nim is 2.257 Å. The macrocyclic dimer complex I is supramolecularly arranged by π-stacking interactions. Computational, Hirshfeld surface analysis and photophysical studies on ligand L and complex I have also been performed. Crystal data for C32H36Ag2Cl2N8O8 (M =947.33 g/mol): Triclinic, space group P-1 (no. 2), a = 9.1714(12) Å, b = 10.4373(14) Å, c = 10.8297(14) Å, α = 112.317(3)°, β = 91.391(3)°, γ = 92.353(3)°, V = 957.3(2) Å3, Z = 1, T = 293.15 K, μ(MoKα) = 1.220 mm-1, Dcalc = 1.643 g/cm3, 10248 reflections measured (4.07° ≤ 2Θ ≤ 53.098°), 3966 unique (Rint = 0.0280, Rsigma = 0.0331) which were used in all calculations. The final R1 was 0.0722 (I > 2σ(I)) and wR2 was 0.2229 (all data).